PENGARUH MOTIVASI TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI DI PT. TELKOM TELEKOMUNIKASI RIAU KEPULAUAN-BATAM - Ramadhan, Adzhari; Wahyuni, Purbudi (Buletin Ekonomi Manajemen, Ekonomi Pembangunan, Akuntansi, 2019)
In this research, a study conducted about how working motivation can influence someone works with the satisfaction aspect as the media. This research was intend to know the influence of working motivation to an employee performance, influence of work satisfaction to an employee performance and how intervening someone satisfaction of their works with influence of their work motivation will do to PT. Telkom Telekomunikasi Riau Kepulauan – Batam workers works. The population on this research is based on all the workers in with the sum of 128 employees. The technic that used for this research is using purposive sampling, which means a technic to selectively choose a sample so the samples will define the whole population even only with 56 employee.Some of its employees are 43 people or 76,8%, over 50 years old as many as 23 respondents or 41,1%, S1 educated as many as 30 respondents or 53,6% with 21-30 years working period there are 30 people or 53,6%. Method used for data gathering is using a questionnaire form. The proposed hypothesis, will be tested statistically with structural equation modelling technic, with the help of SMATPL 3.2.7 program to tested the relation between these three variables. The research resulted with 1) Working motivation significantly influence working satisfaction, 2) Working satisfaction significantly influence employee performance, 3) Working motivations positively influence and significantly to employee work performance and work motivation positively influence and significantly to employee work performance with the media of employee working satisfaction in PT. Telkom Telekomuniasi Riau Kepulauan – Batam. This research implicated how PT. Telkom Telekomuniasi Riau Kepulauan – Batam management rise employee working performance by giving the employee motivation and satisfaction by working with them. The desire to controls and the satisfaction on having partners in works become the major issue that being the concern of management to boost up employee performance.